2018
DOI: 10.1093/pm/pnx336
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Nature of Pain- and Analgesia-Related Content of the United States Medical Licensing Examination (USMLE)

Abstract: Background“The ongoing opioid crisis lies at the intersection of two substantial public health challenges—reducing the burden of suffering from pain and containing the rising toll of the harms that can result from the use of opioid medications” [1]. Improved pain education for health care providers is an essential component of the multidimensional response to both still-unmet challenges [2,3]. Despite the importance of licensing examinations in assuring competency in health care providers, there has been no pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…However, competencies that specifically identify pain medicine-related skills, knowledge, or attitudes are minimal or mostly absent in regulatory requirements for medical graduates in Canada and the UK. A recent review of the United States Medical Licensing Examination found that 15% of questions reviewed (40% of total examination questions) were identified as being fully or partially related to pain [ 71 ]. However, these questions were predominantly focused on assessment of pain rather than knowledge of the nature and context of pain, or implications for safe and effective treatment [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, competencies that specifically identify pain medicine-related skills, knowledge, or attitudes are minimal or mostly absent in regulatory requirements for medical graduates in Canada and the UK. A recent review of the United States Medical Licensing Examination found that 15% of questions reviewed (40% of total examination questions) were identified as being fully or partially related to pain [ 71 ]. However, these questions were predominantly focused on assessment of pain rather than knowledge of the nature and context of pain, or implications for safe and effective treatment [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, access to effective pain management treatments must be improved through adoption of clinical best practices in medical and dental practice and clinical health systems. 28 Third, clinical best practices for pain management should be better incorporated into the routine training of clinicians, 29 with special attention to residency training to meet the needs of patients treated in each specialty. 8,15 Finally, quality care must be adequately reimbursed.…”
Section: Clinical Best Practicesmentioning
confidence: 99%
“…15 Encouraging licensing and education practices that do more to emphasize safe and effective pain assessment and management has the potential to improve pain management and mitigate factors that contribute to the current opioid crisis. 26,441 Health care professionals who prescribe opioids are in a key position to balance the benefits of analgesics against the risk of adverse clinical outcomes. It is estimated that "apart from federal prescribers who are required to be trained, fewer than 20% of the over one million health providers licensed to prescribe controlled substances have training on how to prescribe opioids safely and effectively."…”
Section: Provider Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we were not able to compare the extent to which our assessment of PC items agreed with that of NBME, because the specific percentage of questions within any category is proprietary information. 25 Finally, we made a deliberate decision to focus our recommendations on enhancing the quality of PC content across the step examinations instead of the quantity, both because the optimal amount of content is unknown (e.g., to generate a reportable subscore domain for a given examination) and because multiple specialty and stakeholder societies have advocated for their own interests being represented in the examination series over the years, 26,27 yet the USMLE is structurally limited in how much of any content area can be delivered during an examination period. We hope that our recommendations will allow for integration of PC concepts across a breadth of organ systems and patient populations in a manner that improves the examinations themselves and ultimately medical student and resident PC knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%